2014
DOI: 10.3390/md12052458
|View full text |Cite
|
Sign up to set email alerts
|

Marinopyrrole Derivatives as Potential Antibiotic Agents against Methicillin-Resistant Staphylococcus aureus (III)

Abstract: The marine natural product, marinopyrrole A (1), was previously shown to have significant antibiotic activity against Gram-positive pathogens, including methicillin-resistant Staphylococcus aureus (MRSA). Although compound (1) exhibits a significant reduction in MRSA activity in the presence of human serum, we have identified key modifications that partially restore activity. We previously reported our discovery of a chloro-derivative of marinopyrrole A (1a) featuring a 2–4 fold improved minimum inhibitory con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
23
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 29 publications
2
23
0
Order By: Relevance
“…Various manipulations to 28 and some of its synthetic precursors have allowed access to multiple analogues for SAR studies. 64,65,69,70 The first, and thus far only, synthesis of marinopyrrole B (29) was reported in 2013 by Cheng et al (not shown), whereby the bipyrrole core in this case was instead generated through alkylation of a trihalogenated pyrrole, which underwent further manipulations to complete a Paal-Knorr construction of the second pyrrole ring, a precursor which allowed for the generation of rac-29. 71 Scheme 5: Convergent total synthesis of racemic marinopyrrole A (28).…”
Section: Marinopyrroles: Determination Of Enzymatically-imposed Atropmentioning
confidence: 99%
“…Various manipulations to 28 and some of its synthetic precursors have allowed access to multiple analogues for SAR studies. 64,65,69,70 The first, and thus far only, synthesis of marinopyrrole B (29) was reported in 2013 by Cheng et al (not shown), whereby the bipyrrole core in this case was instead generated through alkylation of a trihalogenated pyrrole, which underwent further manipulations to complete a Paal-Knorr construction of the second pyrrole ring, a precursor which allowed for the generation of rac-29. 71 Scheme 5: Convergent total synthesis of racemic marinopyrrole A (28).…”
Section: Marinopyrroles: Determination Of Enzymatically-imposed Atropmentioning
confidence: 99%
“…This suggests the binding sites contain both hydrogen bond donors and acceptors. Similar to the effects of chlorine‐substituted marinopyrroles, fluorine substitutions in ring B profoundly contribute the antibacterial activity . Compound 72 with 5‐fluorine substitution exhibited the same potency with two‐ to four‐fold improvement in antibacterial activity over the parent compound (±)‐ 23 .…”
Section: Marinopyrrolesmentioning
confidence: 90%
“…Several marinopyrrole derivatives have been synthesized for their potential antibiotic and anticancer activity since the first report of marinopyrroles in 2008 . They include the derivatives from Hughes et al., Nicolaou et al., Cheng et al., Cheng et al., and Li et al . Since the first total synthesis of marinopyrrole A was published in 2010, 13 patents have been filed with the United States and Patent Cooperation Treaty and published by Li‐Qin et al.…”
Section: Marinopyrrolesmentioning
confidence: 99%
See 2 more Smart Citations